Study of Mechanical Properties of Sand Control Screens for Deepwater Applications - Siti Fatimah Bt Abdul Aziz, Siti Fatimah (Universiti Teknologi Petronas, 2009)
Oil and gas are consumed in huge volumes all over the world, every single day. High consumption rates by consumers and depleting reserves have forced the oil and gas industry to look into innovative methods to produce oil. Therefore exploration and production (E & P) activities are now focused at unconventional reservoirs such as sand-prone and deepwater reserves. The current interest in deepwater E & P activities has caused many oil companies to look into researching the best technology for the treatment of deepwater fields. Sand production is also a significant issue with oil and gas production, where formation sand has a tendency to enter the wellbore, thus causing equipment damage and hindered production. Reliable sand control is vital to economic production in many sandstone reservoirs. A sand control screen is a mechanical device used to prevent the entry of formation sand into the wellbore and is suitable for deepwater applications. This project studies the various mechanical properties and designs of sand control screens available in the market for comparison. The results of the comparison will be the first of its kind, giving oil companies such as PETRONAS a comprehensive guide, in terms of technical considerations, to the various sand control screens available in the market. This guide will also be a sales incentive for oil and gas service companies to market their technology to oil companies. The study indicates that sintered laminate (SL) media, porous metal filter (PMF) and drainage support contribute towards enhanced mechanical properties. Case study is conducted using data from existing deepwater field to study past history of sand control applications in the field. Velocity and flow analysis is carried out to evaluate flow rates through the screen during oil and gas production. This project provides an overall outlook towards understanding the relation of mechanical properties and mechanical design of the screen.